2021
DOI: 10.1021/acs.cgd.1c01141
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Organoferroelasticity in a TEMPO Crystal

Abstract: For ferroelastic deformation, twinning facilitates the plastic shape change, leaving spontaneous strain. The twinning is common in metal solids in their microstructures and, recently, has been found in organic solids under a single-crystal state. To actualize multiferroicity in organic molecular materials, the crystals consisting of organic free radicals can be candidates, bringing magnetic properties in organoferroelastic solids. Herein, we demonstrated the organoferroelastic deformation of organic radical cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Eventually, a three-point bending test on a universal testing instrument was used to determine the mechanical strength by measuring the elastic modulus of the crystal (Figure S3, SI). ,, The single crystal was subjected to a 14 MPa stress on the face (001/00) in the three-point bending test at RT (Figure S3, Movie S6, SI). The elastic modulus was calculated from the slope of the stress–strain curve of the single crystal (data conversion based on eq S1 and S2, SI).…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, a three-point bending test on a universal testing instrument was used to determine the mechanical strength by measuring the elastic modulus of the crystal (Figure S3, SI). ,, The single crystal was subjected to a 14 MPa stress on the face (001/00) in the three-point bending test at RT (Figure S3, Movie S6, SI). The elastic modulus was calculated from the slope of the stress–strain curve of the single crystal (data conversion based on eq S1 and S2, SI).…”
Section: Resultsmentioning
confidence: 99%
“…A three-point bending test on a universal testing instrument was used to determine the mechanical strength by measuring the elastic modulus of crystal 1 in relation to temperature 23,57,58 (Fig. S7, ESI †).…”
Section: Elastic Modulus Analysismentioning
confidence: 99%
“…3,6 Shape-memory effects are well perceived in alloys and polymers, designated as shape memory alloys 7 (SMAs) and shape memory polymers (SMPs). 8 With the finding of several mechanical deformations such as elastic and plastic bending, [9][10][11] thermosalient, [12][13][14] light-induced mechanical behavior, [15][16][17] mechanosalient, 18 superelastic, [19][20][21] or ferroelastic deformation [22][23][24][25] in organic molecular crystals, crystalline materials are considered desirable candidates for the development of stimuli-responsive intelligent materials along with properties similar to SMAs and SMPs. The shape transition and recovery process in SMAs is executed by a crystalline phase transition called ''thermoelastic transition'' in-between austenitic and martensitic phases in their microstructure with respect to temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Movie S2: shear stress-induced mechanical deformation on the (001) plane of cocrystal 2 by using a pair of tweezers showed that different crystal structures with polar space groups and weak intermolecular interactions such as weak hydrogen bonding, halogen bonding, and van der Waals interactions contribute to superelastic or ferroelastic deformation. [20][21][22] The inuence of weak intermolecular interactions involving halogen groups such as an aromatic C-F group, [23][24][25][26] and halogenhalogen 27,28 and p stacking interactions [29][30][31] on directing the crystal packing in the presence or absence of strong hydrogen bonds has been extensively studied, and can serve as an excellent tool for crystal designing. Li et al suggested that such crystals could be designed by considering the orientational change of molecules caused by twinning in superelastic and ferroelastic deformation.…”
Section: Introductionmentioning
confidence: 99%